Ecosystem service decline in response to wetland loss in the Sanjiang Plain, Northeast China - Yan, Fengqin; Zhang, Shuwen (Ecological engineering, 2019)
In the last six decades, natural ecosystems in the Sanjiang Plain have undergone significant disturbance. Our study investigated wetland loss history and revealed the ecosystem service decline caused by wetland loss in this area. Based on multi-source data, we obtained wetland loss history since the mid-1950s. Then ecosystem service value (ESV) changes in response to wetland loss were estimated quantitatively in the Sanjiang Plain. Results indicate that wetland area declined by 73.3% (about 2.77 million ha) since 1954, mainly due to the transformation of wetlands to farmland. Wetland loss has reduced the ecosystem service value by $57.46 billion over the past six decades. The largest reduction in ESVs was due to agricultural expansion, especially that of dry farmland. Ecosystem services of all functions except agricultural product functions decreased in the past 60 years. Agricultural product functions increased at the expense of other functions. Wetland restoration and protection of existing wetlands are necessary to reduce the loss of ecosystem services as well as to promote sustainable development.